Biofertilizers Used in Rice Cultivation - Devi, Ayekpam Dollina; Singh, Teekam; Kumari, Megha (Chronicle of Bioresource Management, 2020)
The application of biofertilizers in rice cultivation offers a sustainable alternative to chemical fertilizers, enhancing both crop yield and soil health. Biofertilizers, comprising beneficial microorganisms such as BGA, Azolla, and Azospirillum, facilitate essential processes like nitrogen fixation, supplying N, the major nutrient which is of utmost importance in rice. Moreover, integrating biofertilizers into rice farming practices can reduce environmental pollution associated with excessive chemical fertilizer use, promoting ecological balance. The adoption of biofertilizers not only supports sustainable agriculture but also contributes to long-term soil fertility and productivity. To fully harness the benefit of biofertilizers in rice the right type of biofertilizer should be used in an integrated manner with chemical fertilizers. This avoids yield penalty while addressing environmental concerns.